The Political Economic Roots of Hollywood Strikes, 1950-2023 - James McMahon (notes on cinema, 2024)
This paper investigates the timing of labour strikes in Hollywood. The occurrence of strikes, such as the WGA and SAG-AFTRA strikes in 2023, can make sense when we have the hindsight to piece together the historical details of what created rifts between labour and management. But was 2023 a particularly fragile year for contract negotiations to break down with two of Hollywood's creative labour unions? If labour demands were reasonable, why did studios refuse to agree with them? And if Hollywood studios are profitable, what makes management see the demands of labour as something “unreasonable”? *** This paper uses multiple sources of empirical data to analyse the historical trends of strikes in Hollywood between 1950 and 2023. Strikes in Hollywood — particularly by the WGA and SAG-AFTRA — have common political economic roots. They tend to occur when the profits of major Hollywood studios are in a type of danger zone: when the differential profits of Hollywood are stagnating or declining. Differential profit is a relative measure of performance. Differential profit can be found in any situation where a firm or set of firms holds a better stream of income than what others hold. For example, differential gains still occur when a firm loses profit at a slower rate than others. In the case of the Hollywood studios, differential profit is measured against the largest firms in other business sectors. *** The paper argues that relationships between management and labour in Hollywood are strained by the appearance of these danger zones of differential profit. When the differential profit of Hollywood's major studios falls, the studios are pressured to increase their profits through aggressive methods such as cost-cutting. Data from 2006 to 2022 demonstrate that acts of cost-cutting hurt creative labour significantly more than studio management. As employment in arts, design, and entertainment occupations stagnated, management occupations increased in size around the 2008 WGA strike, as well as during the years before the 2023 WGA and SAG-AFTRA strikes. Management occupations also had higher wage and salary increases than arts, design, and entertainment occupations. *** The paper also argues that alternatives to the aggressive approaches of increasing profits are unlikely to appear in the current business conditions of Hollywood film distribution, even with the growth of streaming media. With few exceptions, Hollywood studios since the 1980s have built a delicate system of risk reduction, which is disrupted by injections of green-field spending and investment. In other words, the major studios currently prefer stagflation over growth, a preference that creates managerial aversions to new employment, significant increases in compensation and other financial benefits in the next collective agreement.
Conference: Society for Cinema and Media Studies (SCMS) Annual Conference, Boston, MA, March 14-17, 2024
Keywords: P1; P12; E31; L82; J52; 330; differential accumulation; dominant capital; Hollywood; power; profit; stagflation; strikes